IS4‐FAM, a fluorescent tool to study CXCR4 affinity and competitive antagonism in native cancer cells - Hamshaw, Isabel; Cominetti, Marco M. D.; Nana‐Akyin, Princess; Yee Ho, Ernie Ho; Searcey, Mark; Mueller, Anja (Pharmacology research & perspectives, 2024)
The ability to accurately measure drug‐target interaction is critical for the discovery of new therapeutics. Classical pharmacological bioassays such as radioligand or fluorescent ligand binding assays can define the affinity or Kd of a ligand for a receptor with the lower the Kd, the stronger the binding and the higher the affinity. However, in many drug discovery laboratories today, the target of interest if often artificially upregulated by means of transfection to modify the host cell's genetic makeup. This then potentially invalidates the assumptions of classical pharmacology affinity calculations as the receptor of interest is no longer at normal physiological densities. The CXCR4 receptor is expressed on many different cancer cell types and is associated with metastasis and poor prognosis. Therefore, the CXCR4 receptor is a desirable target for novel therapeutics. In this study, we explore the applicability of the newly developed fluorescently tagged CXCR4 antagonists, IS4‐FAM as an investigative tool to study CXCR4 affinity and competitive antagonism in native, non‐transfected cancer cells using confocal microscopy and flow cytometry. IS4‐FAM directly labels CXCR4 in several cell lines including high CXCR4 expressing SK‐MEL‐28 (malignant melanoma) and PC3 (metastatic prostate cancer) and lower CXCR4 expressing THP‐1 (acute monocytic leukemia) and was competitive with the established CXCR4 antagonist, AMD3100. This highlights the potential of IS4‐FAM as a pharmacological tool for drug discovery in native cells lines and tissues.